SITUS PERMUKIMAN DAN DESKRIPSI SUKU TERASING TO BUNGGU DI MAMUJU UTARA, SULAWESI BARAT - Bernedeta Apriastuti Kuswarini Wardaninggar (Balai Arkeologi Kalimantan Selatan, 2010)
his study aimed to verify the relationship between material culture with tribal traditions To Bunggu. With the survey method was found at several sites in the form of fragment of pottery, ceramics, ancient tombs and the former building of the mosque. In general, this findings are spread on a flat topography along the foot of the hills and coast, indicating the former settlements of the past. Ethnoarchaeology approach used to interpret a particular form of material culture and harmony settlement use some from of material culture. That study of community residing To Bunggu mountaintop forth the analogy of the traditional forms of community housing and the use of stone axes in moving land farming systems. Similarly, the use of clothing form bark in the manufacturing process using a stone called “batu ike” is still practiced by community To Bunggu. The artifacts to explain how strong the Austronesian influence in the region of South and West Sulawesi.